Investigating the elements influencing the psychological issues of reform school students - Le, Ha Thi Thu; Vu, Truong Vuong; Phan, Long Thanh; Vu, Hang Thi Thuy (Journal of Education and e-Learning Research, 2023)
Reformatory students are those whose deviant behaviors and habits prevent them from receiving education under normal educational conditions. These students frequently lead a careless, undisciplined lifestyle, being unwilling to work and learn eager to play and demanding. Therefore, when they are admitted to reformatories with severe study and lifestyle requirements, they have great psychological difficulty adjusting to their new environment. Students’ psychological issues in adapting to reformatory learning and living regimes are difficult and psychological deficits make it challenging for students to adapt to reformatory learning and living conditions. In Vietnam, 665 students from reformatory schools were polled to determine the causes of psychological issues. According to the findings, a variety of elements contribute to students’ psychological difficulties. Individual student conditions such as health, awareness, attitudes and actions as well as inappropriate habits, living without goals or aspirations, etc. are on the subjective side of the equation. On the objective side are the students’ conditions, family, education and psychological obstacles brought on by less-than-ideal circumstances which will make it more difficult for community students to adapt. Both the new school and society must pay more attention to reformatory students in order to establish the conditions necessary for successful integration into the new school and ultimate readmission into society for these students.